Hamstring Shortness among Undergraduate Students, Using Knee Extension Angle Test - Farhan Ishaque; Saira Bano; Hamna Khan; Suneel Kumar; Saeed Qaiser; Muhammad Asif Khan (Journal of Rawalpindi Medical College)
Objective: To examine the causes and incidence of hamstring tightness/shortness among undergraduate physical therapy students. Cross-sectional study. Institute of Physical Medicine & Rehabilitation, DUHS during the period of Jan 2019 to Jun, 2019.